Rare milkvetch (Astragalus) persistence at a utility-scale solar energy facility in the Mojave Desert - Pereira, Tiffany J.; Karban, Claire C.; Kobelt, Lara A.; Munson, Seth M. (Frontiers in Ecology and Evolution, 2025)
Utility-scale solar energy (USSE) development is driving the projected growth in global renewable energy capacity but comes with environmental tradeoffs. New, alternative construction methods are promoted to minimize impacts to soils, vegetation, and hydrology; however, the disturbance created by these methods requires further investigation. We evaluated the population of a rare annual species, threecorner milkvetch (Astragalus geyeri var. triquetrus), at the Gemini Solar Project in the Mojave Desert, USA, two years after construction. Gemini was required to minimize disturbance in the threecorner milkvetch habitat, providing a unique opportunity to study the plant population and life history characteristics of a rare plant species under novel construction methods. Our objectives were to compare plant population characteristics of threecorner milkvetch inside and outside the Gemini footprint and in different photovoltaic (PV) panel microsites (interspace, panel dripline, under panel). We hypothesized that 1) threecorner milkvetch would have lower survival, reproduction, and growth, and a later phenology, inside compared to outside the facility, and 2) that these negative effects on plant demography and phenology would intensify with increasing proximity to photovoltaic panels in the solar array due to an increasing effect of disturbance and reduction of light and water availability. The results of this 1-year study during a favorable year of rainfall demonstrate the persistence of a rare Mojave annual plant species within an altered environment at a USSE facility. We found that threecorner milkvetch had an earlier phenology, grew larger, and had a higher fecundity at Gemini compared to plants off-site. Survivorship between the two populations, however, was not significantly different. Although growth and reproductive metrics were not correlated with distance to panel, minimal threecorner milkvetch emergence occurred directly under the PV panels and along their driplines, indicating a potential loss of suitable habitat if this pattern becomes more widespread in space or through time. Novel construction techniques for USSE could be considered moving forward to minimize impact on aboveground vegetation and maintain viable seed banks. The results of this study can assist land managers in making decisions about USSE development as the demand grows.